Trans-spliced heat shock protein 90 modulates encystation in Giardia lamblia. - Rishi Kumar Nageshan; Nainita Roy; Shatakshi Ranade; Utpal Tatu (Public Library of Science (PLoS), 2014)
BACKGROUND: Hsp90 from Giardia lamblia is expressed by splicing of two independently transcribed RNA molecules, coded by genes named HspN and HspC located 777 kb apart. The reasons underlying such unique trans-splicing based generation of GlHsp90 remain unclear. PRINCIPLE FINDING: In this study using mass-spectrometry we identify the sequence of the unique, junctional peptide contributed by the 5' UTR of HspC ORF. This peptide is critical for the catalytic function of Hsp90 as it harbours an essential "Arg" in its sequence. We also show that full length GlHsp90 possesses all the functional hall marks of a canonical Hsp90 including its ability to bind and hydrolyze ATP. Using qRT-PCR as well as western blotting approach we find the reconstructed Hsp90 to be induced in response to heat shock. On the contrary we find GlHsp90 to be down regulated during transition from proliferative trophozoites to environmentally resistant cysts. This down regulation of GlHsp90 appears to be mechanistically linked to the encystation process as we find pharmacological inhibition of GlHsp90 function to specifically induce encystation. SIGNIFICANCE: Our results implicate the trans-spliced GlHsp90 from Giardia lamblia to regulate an essential stage transition in the life cycle of this important human parasite.